The Sacrament of Confirmation and Profound Intellectual Disability – A Catholic Perspective - Maliszewska, Anna (Journal of disability & religion, 2021)
Two reasons can be seemingly identified for the fact that people with profound intellectual disabilities tend not to receive the sacrament of Confirmation. One of them seems to be a misguided and ambivalent perception of such people, either frequently considered” innocent saints” not needing sacraments at all, or perceived unworthy of receiving sacraments. The other reason seems to be a lack of adequate recognition of the importance of the sacrament itself. This text identifies the sacrament of Confirmation as crucial both for the very existence and development of every individual member of Christ’s Body.